Educational reform in Algeria - DJERADI, Hafsa; GUESSMIA, Mebrouk (Social Sciences Journal)
Many countries of the world have witnessed change and reform in the educational field, which appeared in different forms and forms. There is a renewal called for by contemporary reformers of the curricula, and Algeria is considered a third world country as a pioneer in reforms in the educational field because the most important element of the educational system is the reform of the educational curricula. From teaching with objectives to teaching with competencies, as the latter moved the various educational stages (primary, intermediate and secondary) and on top of them the primary school, which is considered the first structure - basic education - for the proper continuation of the rest of the educational levels, and the aim of the change in this system is better achievement without spending A great effort, and the exploitation of all human and material capabilities, including training teachers, preparing them, and recruiting them to accept and adapt to this reform. Especially the educational family, and this is due to its novelty and modernity